Nutritional Value, Phytochemical Potential, and Therapeutic Benefits of Pumpkin (Cucurbita sp.) - Maria Batool; Muhammad Modassar Ali Nawaz Ranjha; Ume Roobab; Muhammad Faisal Manzoor; Umar Farooq; Hafiz Rehan Nadeem; Muhammad Nadeem; Rabia Kanwal; Hamada AbdElgawad; Soad K. Al Jaouni; Samy Selim; Salam A. Ibrahim (Plants, 2022)
Pumpkin is a well-known multifunctional ingredient in the diet, full of nutrients, and has opened new vistas for scientists during the past years. The fruit of pumpkin including the flesh, seed, and peel are a rich source of primary and secondary metabolites, including proteins, carbohydrates, monounsaturated fatty acids, polyunsaturated fatty acids, carotenoids, tocopherols, tryptophan, delta-7-sterols, and many other phytochemicals. This climber is traditionally used in many countries, such as Austria, Hungary, Mexico, Slovenia, China, Spain, and several Asian and African countries as a functional food and provides health promising properties. Other benefits of pumpkin, such as improving spermatogenesis, wound healing, antimicrobial, anti-inflammatory, antioxidative, anti-ulcerative properties, and treatment of benign prostatic hyperplasia have also been confirmed by researchers. For better drug delivery, nanoemulsions and niosomes made from pumpkin seeds have also been reported as a health promising tool, but further research is still required in this field. This review mainly focuses on compiling and summarizing the most relevant literature to highlight the nutritional value, phytochemical potential, and therapeutic benefits of pumpkin.